The lipid elongation enzyme ELOVL2 is a molecular regulator of aging in the retina. Issue 2 (14th January 2020) - Chen, Daniel; Chao, Daniel L.; Rocha, Lorena; Kolar, Matthew; Nguyen Huu, Viet Anh; Krawczyk, Michal; Dasyani, Manish; Wang, Tina; Jafari, Maryam; Jabari, Mary; Ross, Kevin D.; Saghatelian, Alan; et al.
Abstract: Methylation of the regulatory region of the elongation of very‐long‐chain fatty acids‐like 2 ( ELOVL2 ) gene, an enzyme involved in elongation of long‐chain polyunsaturated fatty acids, is one of the most robust biomarkers of human age, but the critical question of whether ELOVL2 plays a functional role in molecular aging has not been resolved. Here, we report that Elovl2 regulates age‐associated functional and anatomical aging in vivo, focusing on mouse retina, with direct relevance to age‐related eye diseases. We show that an age‐related decrease in Elovl2 expression is associated with increased DNA methylation of its promoter. Reversal of Elovl2 promoter hypermethylation in vivo through intravitreal injection of 5‐Aza‐2'‐deoxycytidine (5‐Aza‐dc) leads to increased Elovl2 expression and rescue of age‐related decline in visual function. Mice carrying a point mutation C234W that disrupts Elovl2 ‐specific enzymatic activity show electrophysiological characteristics of premature visual decline, as well as early appearance of autofluorescent deposits, well‐established markers of aging in the mouse retina. Finally, we find deposits underneath the retinal pigment epithelium in Elovl2 mutant mice, containing components found in human drusen, a pathologic hallmark of age related macular degeneration. These findings indicate that ELOVL2 activity regulates aging in mouse retina, provide a molecular link between polyunsaturated fatty acids elongation and visual function, and suggest novel therapeutic strategies for the treatment of age‐related eye diseases. Abstract : Upon Elovl2 mutation autofluorescent spots can be observed in mutant but not in wild‐type littermates.